Influence of type of final restoration on the fracture resistance and fracture mode of endodontically treated premolars with occluso-mesial cavities - Salwa Omar Bajunaid; Norah Omar AlSadhan; Noura AlBuqmi; Reem Alghamdi (Elsevier, 2021)
Introduction: The aim of this study was to compare the fracture resistance of endodontically treated premolars after the application of three restorative materials (i.e., direct composite, indirect composite, and computer aided design/computer aided manufacturing CAD/CAM ceramic inlays) to restore a conservative occluso-mesial cavity preparation. Materials and methods: sixty sound maxillary premolars were divided into four experimental groups; group A: the control group, where neither root canal treatment nor preparation were performed; group B: teeth were restored with a direct Filtek Z250 composite restorative material; group C: teeth were restored with an indirect inlay Filtek Z250 composite restorative material; group D: teeth were restored with IPS E.Max CAD/CAM monolithic ceramic inlays. Access cavities and root canal treatment procedures were conducted using standard techniques. Then, the cavities were restored with direct composite restorative materials following manufacturer's instructions. Each group received mesial-occlusal cavities and restored according to the designated group.Teeth from all groups were exposed to a thermocycling regimen of 500 cycles in water baths at 5-55 °C. Then, each specimen was mounted on a special fixture on a computer controlled Instron Universal Testing Machine. An axial compressive load was applied to the palatal cusp up to failure at an angle of 45°. The force was applied at the rate of 2 mm/min until visible or audible evidence of fracture was observed. The force at fracture was measured in MPa, and the fracture mode was recorded as either favorable [restorable adhesive fracture above the cemento-enamel junction (CEJ)] or unfavorale (non-restorable fractures under CEJ). The obtained data were analyzed using the SPSS version 21.0 statistical software. One-way ANOVA and Tukey's test were used to compare the mean values of maximum load of the four groups. Pearson's Chi-square test was used to compare the distribution of failure mode among the four groups. The p-value of ≤ 0.05 was used to report the statistical significance of results.